Mathematical devices for optical sciences - Başkal, Sibel; Kim, Y. S.; Noz, Marilyn E. (IOP (Series). Release 6., 2019)
The Lorentz group which is the underlying scientific language for modern optics has been most notably used for understanding Einstein's special relativity. By using a simplified approach of two-by-two matrices and Wigner functions, this book provides a basic and novel approach to classical and quantum optics, making these often-difficult subjects more transparent to the reader. Written by three experts in the field, Professors Sibel Başkal, Young S. Kim, and Marilyn E Noz, this book will give the reader a comprehensive overview of how fundamental issues in quantum mechanics can be approached using various optical instruments, Wigner functions, and quantum entanglement.